Tensions around including persons with diagnosis of dementia in scientific research - Gajardo Jáuregui, Jean; Aravena, José Miguel (Acta Bioethica, 2017)
Dementia —Major Neurocognitive Disorder— features cognitive impairment and other behavioral and psychological symptoms that impact the person’s capacity to respond effectively to the environmental demands. The number of persons with dementia is consistently increasing in the world and therefore has become a public health priority that urges the development of strategies to address its impact. Biomedical, clinical and psychosocial scientific research in dementia must be part of any dementia strategy. Dementia research raises bioethical issues and people with dementia are often excluded from research. This article seeks to synthesize relevant elements related to the inclusion of persons with dementia in research from different perspectives, including the impact of cognitive impairment and local jurisprudence. Bioethical dilemmas in dementia research involve, among others, the determination of capacity to consent. Chilean laws 20.120 and 20.084 rise controversies in the case of disability that relate directly to participation of persons with dementia in researching. This manuscript seeks to contribute with a synthesis of key elements for the analysis of the participation of persons with dementia in scientific research.